The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.fishres.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interactive effects of air exposure duration and water temperature on the condition and survival of angled and released fish

Abstract: At present, there is a reasonable understanding of the independent effects of catch-and-release (C&R) angling stressors, such as air exposure and water temperature, on endpoints such as physiological disturbance, behavioural impairment and mortality. However, little is known about the multiplicative or interactive nature of these different C&R stressors. This study used bluegill (Lepomis macrochirus) as a model to evaluate the combined effects of water temperature and air exposure on fish behaviour, equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
172
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(184 citation statements)
references
References 49 publications
(43 reference statements)
11
172
1
Order By: Relevance
“…This large variability is influenced by multiple factors, including season, fishery sector, geographical region, and water depth, and is further convoluted by interactions among these factors (Gingerich et al 2007). Moreover, the majority of these studies have only assessed immediate discard mortality, or mortality that is observed from surface observations within several seconds postrelease, while delayed mortality is unknown.…”
mentioning
confidence: 99%
“…This large variability is influenced by multiple factors, including season, fishery sector, geographical region, and water depth, and is further convoluted by interactions among these factors (Gingerich et al 2007). Moreover, the majority of these studies have only assessed immediate discard mortality, or mortality that is observed from surface observations within several seconds postrelease, while delayed mortality is unknown.…”
mentioning
confidence: 99%
“…Other studies report even low levels of stress resulting from increased water temperature can cause noticeable changes in behavior (e.g. loss of equilibrium, impaired swimming ability) [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…angling induced injury, barotrauma, or exhaustion) and delayed (within five days of angling) mortality. In numerous studies, high levels of angling or hauling (transport in a livewell or other enclosure) induced stress was linked to an increased likelihood of delayed mortality [8,9,15]. Mortality due to air exposure did not correspond to changes in blood chemistry among commercially captured Pacific halibut (Hippoglossus stenolepis) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors have been the subject of numerous studies in recent years and include hook type or size (Aalbers et al, 2004;Butcher et al, 2008;Cooke et al, 2005;Graves and Horodysky, 2008;Grixti et al, 2007;Mapleston et al, 2008), hooking location (Alós et al, 2008;Butcher et al, 2007;McGrath et al, 2009;Pope and Wilde, 2004), landing apparatus (Barthel et al, 2003;Danylchuk et al, 2008;De Lestang et al, 2008) and duration of exposure to air (Gingerich et al, 2007;Reynolds et al, 2009).…”
Section: Introductionmentioning
confidence: 99%